Exclusive branching-fraction measurements of semileptonic tau decays into three charged hadrons, into phi pi(-)nu(tau), and into phi K(-)nu(tau) - Aubert, B; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Chen, J; et al. (2008)
Using a data sample corresponding to an integrated luminosity of 342fb-1 collected with the BABAR detector at the SLAC PEP-II electron-positron storage ring operating at a center-of-mass energy near 10.58 GeV, we measure B(τ-→π-π-π+ντ(ex.KS0))=(8.83±0.01±0.13)%, B(τ-→K-π-π+ντ(ex.KS0))=(0.273±0.002±0.009) %, B(τ-→K-π-K+ντ)=(0.1346±0.0010±0.0036)%, and B(τ-→K-K-K+ντ)=(1.58±0.13±0.12)×10-5, where the uncertainties are statistical and systematic, respectively. These include significant improvements over previous measurements and a first measurement of B(τ-→K-K-K+ντ) in which no resonance structure is assumed. We also report a first measurement of B(τ-→ π-ντ)=(3. 42±0.55±0.25)×10-5, a new measurement of B(τ-→ K-ντ)=(3.39±0.20±0.28)×10-5 and a first upper limit on B(τ-→K-K-K+ντ(ex.)). © 2008 The American Physical Society.